Development of attentional bias towards visual word forms in the environment in preschool children. Issue 3 (16th March 2022) - Qing, Tianying; Xiao, Ying; Xue, Huidong; Wang, Wei; Ye, Ming; Hu, Jing; Xue, Licheng; Chen, Bing; Lv, Yating; Zhao, Jing
ABSTRACT: Environmental prints (e.g., the name "Mcdonald's" on advertising boards) provide a visual environment rich in written words at the early stage of learning to read. Children's attention to words is closely related to the process of learning to read. However, what remains unclear is how children's attention to words in environmental prints develops and is related to their reading ability before conventional reading training begins. Using the eye-tracking technique, the present study examined the early development of attention to words in environmental prints. Four-, five-, and six-year-old preschool children were tested. We transformed the original format of each environmental print into three versions with gradually minimized contextual cues (i.e., colour, logo, and font type). The results showed that attentional bias towards words increases with age even before conventional reading training. Moreover, it appears that a rapid increase occurs between the ages of four and five. The logo cue (rather than colour cue or font type cue) has a salient effect on the attentional bias towards words. Attentional bias towards words is increased with children's reading ability.